Development of criteria and indicators for forest plantations from assessment toward communication tools for management - Guizol, P.; Muhtaman, D.R. (Gadjah Mada University, Faculty of Forestry, 2001)
The rapid loss of forest resources from teak plantations in Java is a serious problem that is raising interest in finding new systems of management that will ensure sustained availability of resources. At the same time, all around the world a growing number of stakeholders are becoming involved in forest management. Sustainable forest management (SFM) has become the goal for many countries and stakeholders. But the definition of sustainability may differ significantly among stakeholders, who often have different perceptions and interests. Achieving a common definition of sustainability is the first step needed for stakeholders involved in forest management to reach agreement on goals. An impressive amount of work has already been done to develop criteria and indicators (C&I) for forest sustainability. CIFOR's pioneering work in this area has included efforts to develop a set of C&I for forest plantations. This article describes the process involved in developing these C&I. The process is collaborative and cross-disciplinary, and particularly aims to improve the communication among experts.